2019
DOI: 10.17921/2447-8938.2019v21n3p264--268
|View full text |Cite
|
Sign up to set email alerts
|

Active Teaching Methodology Applied in the Training of Undergraduate Dental Students: Use of Video-Lesson

Abstract: The goal of the present study was to evaluate the effectiveness of the active video-class methodology in the teaching-learning process, ascertaining the understanding, clarity and absorption through a pre structured questionnaire. The sample consisted of 35 students, who were enrolled in the fixed prosthesis discipline, between the age of 19 and 31 years old. A videotape with provisional crown content was applied to the sample and, after a pre-structured questionnaire with 5 questions with objective and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The finding indicated that the dimension of learning anxiety significantly improved once the Escape Room was applied as a tool for teaching mathematics, this seem to be consistent with Parra -González et al ( 2020 ), whose found that Escape Room enhanced students’ ability to manage their learning anxiety. According to the numbers above we can see that students were more motivated and showed a higher level of learning anxiety, consistent with other works, and this is because of the positive intervention of the Escape Room, which meant they felt less annoyed, hostile, or frustrated while performing the activities or tests proposed by the teacher (Santos et al, 2019 ), and they perceived themselves as protagonists and were interested in the tasks that needed to be performed (Pérez-Manzano & Almela-Baeza, 2018 ), they performed instructional tasks repeatedly without fear of error (Contreras Espinosa, 2016 ; Lee, & Hammer, 2011 ), and they built on their own knowledge with this type of methodology (Khalil & Elkhider, 2016 ; Pumilia-Gnarini, 2013 ). Consequently, this contributed to lower anxiety and stress, since they could perform tasks at their own pace, autonomously, and individually, according to their personal and cognitive peculiarities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding indicated that the dimension of learning anxiety significantly improved once the Escape Room was applied as a tool for teaching mathematics, this seem to be consistent with Parra -González et al ( 2020 ), whose found that Escape Room enhanced students’ ability to manage their learning anxiety. According to the numbers above we can see that students were more motivated and showed a higher level of learning anxiety, consistent with other works, and this is because of the positive intervention of the Escape Room, which meant they felt less annoyed, hostile, or frustrated while performing the activities or tests proposed by the teacher (Santos et al, 2019 ), and they perceived themselves as protagonists and were interested in the tasks that needed to be performed (Pérez-Manzano & Almela-Baeza, 2018 ), they performed instructional tasks repeatedly without fear of error (Contreras Espinosa, 2016 ; Lee, & Hammer, 2011 ), and they built on their own knowledge with this type of methodology (Khalil & Elkhider, 2016 ; Pumilia-Gnarini, 2013 ). Consequently, this contributed to lower anxiety and stress, since they could perform tasks at their own pace, autonomously, and individually, according to their personal and cognitive peculiarities.…”
Section: Discussionsupporting
confidence: 88%
“…As claimed by researchers, there has been a significant increase in the application of Escape Rooms as learning environments (Shute & Ke, 2012 ), with positive outcomes reported (Hursen & Bas, 2019 ). Hence, the notion of activation is considered to be where the learner participates in the process of learning by acquiring new knowledge on their own (Santos et al, 2019 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, activation is understood here as the state of the learner and how he/she faces the task, and his/her personal predisposition to achieve the goals and objectives envisaged by the educational task. Therefore, the concept of activation is understood as active participation of a learner in the learning process by learning something new themselves [48].…”
Section: Escape Room As a Gamification Methodological Strategymentioning
confidence: 99%